ANALISIS STRUKTUR BATIN PUISI “DI TOILET ISTANA” KARYA RADHAR PANCA DAHANA - Ahmad Hendra Komara; Tati Purwasih; Eli Syarifah Aeni (IKIP Siliwangi, 2019)
This research is motivated by the curiosity of research on the poetry of a Radhar Panca Dahana which makes poetry a vehicle for criticizing a political phenomenon that exists in the government. Politics and poetry are two things that are difficult to find correlation. Through this poem